QbD based synthesis and characterization of polyacrylamide grafted corn fibre gum. (20th January 2017) - Singh, Akashdeep; Mangla, Bhumika; Sethi, Sheshank; Kamboj, Sunil; Sharma, Radhika; Rana, Vikas
Highlights: A 3 2 full factorial design was used for the synthesis of polyacrylamide corn fibre gum. The graft copolymer revealed shear thinning behaviour and Herschel-Bulkley model. The mucoadhesive strength was higher than karaya, moringa oleifera and xanthan gum. The viscoelastic analysis suggested liquid like viscous liquid. Abstract: The aim of present investigation was to utilize quality by design approach for the synthesis of polyacrylamide corn fibre gum (PAAm -g- CFG) from corn fibre gum (CFG) by varying concentration of acrylamide and initiator. The spectral analysis (ATR-FTIR, 1 H NMR, DSC, X-ray and Mass spectroscopy) was conducted to assure grafting copolymerization of CFG with acrylamide. The powder flow properties confirm the porous nature of PAAm- g -CFG. The grafted copolymer dispersion showed shear thinning behaviour that follows Herschel Bulkley model. The viscoelastic analysis suggested viscous liquid like nature of PAAm- g -CFG and its viscosity increases with increase in concentration of PAAm- g -CFG. The mucoadhesive strength of synthesized PAAm- g -CFG was found to be higher than moringa oleifera gum, karaya gum, guar gum, xanthan gum, chitosan and gelatin. Further, the results pointed toward enhanced thermal stability of PAAm- g -CFG. Thus, PAAm- g -CFG has a great potential to be used in food and pharmaceutical industry.